Island as an Unreachable Destination: Umberto Eco’s The Island of the Day Before (1994) - Rama Kundu (Interlitteraria, 2016)
An island, owing to its very isolation, has accumulated layers of significances as an image, and turned out in course of time to be a multivalent sign, which has been adapted by writers and artists across lands and ages to articulate a rich spectrum of ideas, discourses, and counterdiscourses. In our times Umberto Eco, in a story, located in the mid-seventeenth century, and placed upon a non-space – neither land, nor water, nor air – for its backdrop, has offered yet another unusual approach to this unique signifier by means of installing a fresh paradigm of voyage and [non]arrival at an island, Umberto Eco’s The Island of the Day Before is a story about a search for ‘Terra Incognita’, for ‘the Island not Found’, and an impossible venture, ‘to find the Unfindable’. In spite of the crowded ideas, obscure references and antique time-space continuum the book exerts its own charm upon today’s reader. Some of the perennial themes addressed here are love, life, death, ‘Time’ and God, – and the unreachable island, which is so near, yet remains so far, serves as the pivotal point of this revolving, multi-modal mirror. By means of a superb feat of imaginative flight the dream-element of the situation has been reinforced by the metanarrator as he goes on reconstructing the scraps left behind by the precursor micro-narrator. The hyperreality of Roberto’s specific oxymoronic island , along with its ‘distant proximity’, is accentuated by the dream-tenor of the narrative as well as by covert/and overt mythical allusions, which have been lying strewn about unmistakably. Myths embrace and intersect one another across disparate cultural frames. Eco presents a fantasy island in the garb of mystic knowledge disseminated by a supposedly medieval theologiancum- scientist. The micro-narrator’s search is simultaneously about the Island of Solomon and the longitude, the hundred-eightieth meridian, both belonging to the ‘terra incognita’. The theological notion and the (pseudo) scientific concepts (of the 17th century) seem to be interchangeable variables in the context. At one level it is about ‘the Island not found’, not findable, and the protagonist’s paradoxical voyage for the same. How could one reach the unreachable! And yet, who knows! The reader is left only to imagine and wonder about this postmodern Odysseus who has no home, no kin, no land to rest his feet upon, no mission (which has been lost, along with the wrecked ship, in course of the voyage), and finally no destination even.